2018
DOI: 10.1371/journal.pone.0197256
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota composition is altered according to nutritional biorhythms in the leopard coral grouper (Plectropomus leopardus)

Abstract: Aquaculture is currently a major source of fish and has the potential to become a major source of protein in the future. These demands require efficient aquaculture. The intestinal microbiota plays an integral role that benefits the host, providing nutrition and modulating the immune system. Although our understanding of microbiota in fish gut has increased, comprehensive studies examining fish microbiota and host metabolism remain limited. Here, we investigated the microbiota and host metabolism in the coral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…The gut microbes of freshwater fish are commonly dominated by phyla Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria 51,52 . Firmicutes, Bacteroidetes, and Teniricutes are defined as the beneficial bacteria of the gut and their positive role in growth performance, immunity, digestion and disease resistance of aquatic animals [53][54][55][56] . Additionally, they also play an influential role in augmentation of other beneficial bacteria in the gut [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbes of freshwater fish are commonly dominated by phyla Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria 51,52 . Firmicutes, Bacteroidetes, and Teniricutes are defined as the beneficial bacteria of the gut and their positive role in growth performance, immunity, digestion and disease resistance of aquatic animals [53][54][55][56] . Additionally, they also play an influential role in augmentation of other beneficial bacteria in the gut [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a depletion of nutrients induces changes in gut microbiota composition to favor bacterial species/communities that use more diverse energy sources and are capable of survival under limited nutrient conditions (52). Microbiota gut diversity and richness are usually higher under feeding conditions than under fasting conditions as seen in zebrafish (58) and in leopard coral grouper ( Plectropomus leopardus ) (104). In grouper, the dominant phyla are Proteobacteria in fasting and Firmicutes in fed conditions (104) and in the Asian seabass, Lates calcarifer , fasting induces a significant enrichment of Bacteroidetes and a depletion of Betaproteobacteria (105).…”
Section: Factors Affecting Fish Gut Microbiotamentioning
confidence: 99%
“…In recent years, next-generation high-throughput sequencing has shed new light onto the complexity of prokaryotic biodiversity, increasing our understanding of ecological functions between the gut microbiota and its host. Many studies have shown that high microbial diversity levels in the gastrointestinal tract are critical for host nutrition (Hassaan et al, 2017; Li et al, 2017; Mekuchi et al, 2018); disease prevention and immune responses (Milligan-Myhre et al, 2016; Feng et al, 2018); and growth and development (Hill et al, 2016; Egerton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%